2014
DOI: 10.1016/j.bbrc.2014.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 is induced by hypoxia inducible factor in rat alveolar epithelial cells

Abstract: Alveolar type II (ATII) cells remain differentiated and express surfactant proteins when cultured at an air-liquid (A/L) interface. When cultured under submerged conditions, ATII cells dedifferentiate and change their gene expression profile. We have previously shown that gene expression under submerged conditions is regulated by hypoxia inducible factor (HIF) signaling due to focal hypoxia resulting from ATII cell metabolism. Herein, we sought to further define gene expression changes in ATII cells cultured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Using an ischemic mouse model, Durukan et al (34) revealed that STC1 was elevated under hypoxic condition and it was proven that STC1 was dispensable for functional recovery after ischemic stroke. Moreover, hypoxic conditions can induce the expression of STC1, and high expression of STC1 can enhance neuronal resistance to hypoxia (35). It has been demonstrated that hypoxic microenvironments are common in glioma tissues (35).…”
Section: Discussionmentioning
confidence: 99%
“…Using an ischemic mouse model, Durukan et al (34) revealed that STC1 was elevated under hypoxic condition and it was proven that STC1 was dispensable for functional recovery after ischemic stroke. Moreover, hypoxic conditions can induce the expression of STC1, and high expression of STC1 can enhance neuronal resistance to hypoxia (35). It has been demonstrated that hypoxic microenvironments are common in glioma tissues (35).…”
Section: Discussionmentioning
confidence: 99%
“…Both stc-1 and ct were found to be expressed before 1 dpf, and continued to be expressed over development (Lafont et al, 2011;Tseng et al, 2009). Hypoxic treatment was reported to stimulate STC-1 mRNA and/or protein levels in various mammalian cell lines (Ito et al, 2014;Yeung et al, 2005). Additionally, we identified a putative hypoxia-regulatory element (HRE) in the upstream region of the stc-1 gene (data not shown).…”
Section: Impact Of Hypoxia Exposure On Ionic Regulationmentioning
confidence: 90%
“…STC1 expression has also been shown to be influenced by hypoxia. [2][3][4] Hypoxia can also change actin organization, 51 increase focal adhesions, 51 and activate RhoA and ROCK signaling. 52 Whether the change in STC1 expression under hypoxia is regulated through the same zyxin and actin-myosin dependent pathway as described here remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus was produced in human embryonic kidney 293FT (HEK) cells.HEK cells were seeded at 60 000 cells/cm2 in a 10-cm TCP dish in DMEM + 10% FBS. HEK cells were transfected with pMDLg pRRE, pMD2.G, pRSV Rev (Addgene), and one of the pLKO.1 shRNA plasmids using lipofectamine 2000 (Thermo Fisher Scientific) in a ratio of 5:1 (μL lipofectamine 2000:μg DNA) 24 hours after seeding.…”
mentioning
confidence: 99%